Cardiopulmonary Rehabilitation in Pediatric Patients With Congenital and Acquired Heart Disease. Issue 6 (November 2020) - McBride, Michael G.; Burstein, Danielle S.; Edelson, Jonathan B.; Paridon, Stephen M.
Abstract : Background: Heart disease in children and adolescents is common, approaching 1.0% of the population. In those patients with complex physiology and severe cardiac dysfunction, the inability to participate in physical activity results in significant obstacles to normal acts of daily living and significantly diminished quality of life. Attempts to study the practicality and benefits of cardiopulmonary rehabilitation (CR) programs in this population have been hampered by the heterogeneity of lesions, lack of facilities, and trained personnel to supervise these types of programs. Although there are numerous articles on CR in children with cardiac disease, all suffer from the same basic problems of small sample size, short duration of study, and heterogeneous study populations. Purpose: The purpose of this review was to first evaluate the current rehabilitation literature on both congenital cardiac defects and acquired abnormalities—in this latter group placing a significant emphasis on cardiomyopathies, as well as the special populations in the peri-transplant period and/or mechanical circulatory support. Second, we discussed what is known about practical approaches to CR for the various types of pediatric-specific cardiac conditions. This limited data will be supplemented by the current approach of our institution to CR in these populations with the understanding that this is by no means a consensus approach to these patients. Finally, we summarized research goals for this growing group of patients. Conclusion: Cardiopulmonary rehabilitation in pediatric congenital and acquired heart disease is currently a field in its infancy. Significant strides have been made for complex heart disease and impaired myocardial function. Current research holds the promise for the development of programs that are practical, scalable, and can be implemented in most clinical sites within the foreseeable future. Abstract : Heart disease in children and adolescents is often complex and limits physical activity and quality of life. The purpose of this article is to review the current rehabilitation literature on both congenital and acquired cardiac abnormalities including cardiomyopathies and mechanical circulatory support. Practical approaches to cardiopulmonary rehabilitation for the various types of pediatric-specific cardiac conditions are discussed.